Teachers’ perceptions of Content and Language Integrated Learning (CLIL) in primary schools in Andalusia - Szczesniak, Anna Grazyna; Muñoz-Luna, Rosa María (Universidad de Granada, 2022)
Content and Language Integrated Learning (CLIL) has been deemed to be a promising and innovative approach to teaching foreign languages and has received unani-mous endorsement by virtually all educational authorities in the European Union. Yet, not-withstanding the numerous benefits the programme offers, it is not free from difficulties. Thus, the main objective of this qualitative study was to examine the teachers’ perceptions of CLIL implementation with the major focus on the shortcomings detected and outlined in the previous studies. Data were obtained from an ad hoc online questionnaire filled out by 203 in-service teachers from bilingual English primary schools in the eight provinces of Andalusia (i.e., Almería, Cádiz, Córdoba, Granada, Huelva, Jaén, Málaga and Sevilla) in the year 2020. The picture emerging from the results of the study is not positive as it reflects growing concern over the paucity of teacher training programmes, insufficient coordina-tion, lack of attention to diversity, inadequate textbook design, and above all, students’ low English proficiency and class size, factors which might impede the proper development of the programme. Moreover, content teachers as well as those with lower language competen-ce and less experience in teaching appear to be in dire need of more training and support. These findings merit further consideration and should govern educational decisions in order to ensure the feasibility of the project.
https://revistaseug.ugr.es/index.php/portalin/politicaeditorial
Keywords: Educación bilingüe; Lengua inglesa - Estudio y enseñanza - Extranjeros; CLIL; Bilingual education; Implementation; Teachers' perspectives; Andalusia